Logic Programming to Predict Cell Fate Patterns and Retrodict Genotypes during Organogenesis - Hall, Ben; Jackson, Ethan; Hajnal, Alex; Fisher, Jasmin (Royal Society Interface 11: 0140245, 2014)
Logic Programming to Predict Cell Fate Patterns and Retrodict Genotypes during Organogenesis. Magazine article.